Myostatin (MSTN) Gene Indel Variation and Its Associations with Body Traits in Shaanbei White Cashmere Goat - Bi, Yi (Animals (Basel), 2020)
SIMPLE SUMMARY: As a major gene to regulate the muscle mass of animals, Myostatin (MSTN) plays a negative role in regulating the number and size of skeletal myocytes. Additionally, it is reported that mutations of MSTN gene contribute to the double-muscling (DBM) phenomenon. Therefore, mutations of MSTN gene will always be one of the hot spots. A 5 bp indel (c. –120 ins) in the 5’ untranslated region (5’ UTR) of goat MSTN gene was reported to relate to the growth traits of goat. However, all the sample sizes were limited. Herein, this study firstly enlarged the sample size (n = 1074, Shaanbei White Cashmere goat) to uncover the indel location, as well as its association with growing performance. Based on the data, the 5 bp insertion mutation in goat MSTN gene was significantly associated with the body height, height at hip cross, and chest width index in SBWC (p < 0.05), hinted that this insertion could be assigned to an effective molecular marker for growth trait in goat rearing. ABSTRACT: Myostatin (MSTN) gene, also known as growth differentiation factor 8 (GDF8), is a member of the transforming growth factor-beta super-family and plays a negative role in muscle development. It acts as key points during pre- and post-natal life of amniotes that ultimately determine the overall muscle mass of animals. There are several studies that concentrate on the effect of a 5 bp insertion/deletion (indel) within the 5’ untranslated region (5’ UTR) of goat MSTN gene in goats. However, almost all sample sizes were below 150 individuals. Only in Boer goats, the sample sizes reached 482. Hence, whether the 5 bp indel was still associated with the growth traits of goats in large sample sizes which were more reliable is not clear. To find an effective and dependable DNA marker for goat rearing, we first enlarged the sample sizes (n = 1074, Shaanbei White Cashmere goat) which would enhance the robustness of the analysis and did the association analyses between the 5 bp indel and growth traits. Results uncovered that the 5 bp indel was significantly related to body height, height at hip cross, and chest width index (p < 0.05). In addition, individuals with DD genotype had a superior growing performance than those with the ID genotype. These findings suggested that the 5 bp indel in MSTN gene are significantly associated with growth traits and the specific genotype might be promising for maker-assisted selection (MAS) of goats.